Corporate bankruptcy. Tools, strategies and alternatives - NEWTON, Grant W (John Wiley & Sons, 2003)
No company should proceed toward a possible bankruptcy claim without a thorough understanding of the implications of all the available options. Corporate Bankruptcy provides CEOs, CFOs, controllers, and treasurers, as well as financial advisors and other professionals involved with bankruptcy filing, the tools they need to succeed.